PERDAMAIAN DALAM KEBERAGAMAN DITINJAU DARI PERSPEKTIF AL-QUR'AN DAN BIBLE - Zunly Nadia (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
Peace is one of the main teachings in Islam. As a holy book, the Qur'an and the Bible, the guidelines for its adherents to always love the peace. In both scriptures contains many verses that tell people to continue to realize peace on earth. Nevertheless it can not be denied that in both books also revealed verses about war. In this paper the author seeks to explain how the concept of peace in the perspective of the Qur'an and the Bible. The author only describes the concept of peace in the Qur'an as a holy book for Muslims and the Bible as the guidebook of Christians. This article concludes that to achieve that peace, there must be an awareness of religious plurality by respecting the existence of another religion which is of great importance in the religious context in Indonesia which is composed of various religions.